# Math

posted by on .

how do you do this??

-4x-7=-2(x+3)

• Math - ,

-4x-7=-2(x+3)

Multiply -2 by each term inside the parenthesis (x+3).

-4x-7=(-2(x)-2(3))

Complete the multiplication of -2 by each term inside the parenthesis.

-4x-7=(-2x-6)

Remove the parenthesis around the expression -2x-6.

-4x-7=-2x-6

Since -2x contains the variable to solve for, move it to the left-hand side of the equation by adding 2x to both sides.

-4x-7+2x=-6

Since -4x and 2x are like terms, subtract 2x from -4x to get -2x.

-2x-7=-6

Since -7 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 7 to both sides.

-2x=7-6

Subtract 6 from 7 to get 1.

-2x=1

Divide each term in the equation by -2.

Simplify the left-hand side of the equation by canceling the common terms.

Simplify the right-hand side of the equation by simplifying each term.
therefore x = -1/2

### Answer This Question

 First Name: School Subject: Answer:

### Related Questions

More Related Questions

Post a New Question